المدخل التواصلي في تعليم أنشطة اللغة العربية سنة أولى متوسط دراسة ميدانية في بعض متوسطات الوادي - بن خليفة, طويل, راضية هاجر (Univercty of Eloued, 2020)
تهدف الدارسة إلى البحث في أحد المداخل التعليمية الحديثة, والتي تركز على ضرورة الانتقال من التعليم التقليدي للغة إلى التعليم الحديث, والذي يركز على ضرورة إكساب المتعلم القدرة على تجنيد وتوظيف المعارف في المواقف التواصلية الطبيعية, هذه الأخيرة دفعت بنا إلى اختيار دارسة أهم مدخل يسعى إلى تحقيق هذا الهدف, وهو المدخل التواصلي حيث ركزنا في مدى تطبيقه في أنشطة اللغة العربية المقررة على تلاميذ سنة أولى متوسط, ولتحديد دور التواصل وأهميته قمنا بعد التنظير لمقتضيات البحث بدارسة تحليلية لأنشطة اللغة العربية, مبينين تجليات المدخل التواصلي فيها ومدى توافر عناصره وتكاملها لتحقيق نجاح العملية التعليمية التواصلية, وأرفقنا هذا التحليل بدارسة ميدانية شملت استجواب عينة من أساتذة اللغة العربية, الذين أفادو بدورهم من خلال ملاحظاتهم واقتارحاتهم لتفعيل هذا المدخل في تعليم أنشطة اللغة العربية, وإنتاج متعلم يجيد تطبيق آليات المدخل التواصلي لضمان ايصال رسالته وخطابه دون تشويش ,بل لنجاح العملية التواصلية في أرقى صورها . The study aims to investigate one of the modern educational approaches which focuses on the necessity of moving from traditional language education to modern education. It focuses on the learner's need to acquire the ability to use the knowledge in natural communicative situations. This latter pushed us to choose the most important approach to reach the goal which is the communicative approach. we focused on its application in the Arabic language activities for first-year middle school pupils. After dealing with the theoretical part of the research requirements, We conducted an analytical study of the activities of the Arabic language to determine the role of communication and its importance, showing the existance of the communicative approach and the availability of its elements to achieve the success of the communicative educational process. We also designed a questionnaire to be answered by a sample of Arabic language teachers who gave good remarks and beneficial suggestions to activate this approach in teaching Arabic language activities and producing a learner who can apply the mechanisms of the communicative approach to ensure the delivery of his message and speech without interference which leads to the success of the communicative process in its finest form
Keywords: الأنشطة , المدخل التواصلي, التعليم; activities, communicative portal, education